Diabetes and disordered bone metabolism (diabetic osteodystrophy): time for recognition. Issue 6 (June 2016) - Epstein, S.; Defeudis, G.; Manfrini, S.; Napoli, N.; Pozzilli, P.
Abstract Summary Diabetes and osteoporosis are rapidly growing diseases. The link between the high fracture incidence in diabetes as compared with the non-diabetic state has recently been recognized. While this review cannot cover every aspect of diabetic osteodystrophy, it attempts to incorporate current information from the First International Symposium on Diabetes and Bone presentations in Rome in 2014. Diabetes and osteoporosis are fast-growing diseases in the western world and are becoming a major problem in the emerging economic nations. Aging of populations worldwide will be responsible for an increased risk in the incidence of osteoporosis and diabetes. Furthermore, the economic burden due to complications of these diseases is enormous and will continue to increase unless public awareness of these diseases, the curbing of obesity, and cost-effective measures are instituted. The link between diabetes and fractures being more common in diabetics than non-diabetics has been widely recognized. At the same time, many questions remain regarding the underlying mechanisms for greater bone fragility in diabetic patients and the best approach to risk assessment and treatment to prevent fractures. Although it cannot cover every aspect of diabetic osteodystrophy, this review will attempt to incorporate current information particularly from the First International Symposium on Diabetes and Bone presentations in Rome in November 2014.